Sistem Deteksi Dini Kebakaran berbasis IoT dengan Integrasi Database dan Aplikasi Android untuk Pengawasan Lingkungan pada Al Bumi It Store - Muhammad Iyas Kustiantoro; Dendy Kurniawan; Bagus Sudirman; Edy Siswanto; Ahmad Ashifuddin Aqham (Universitas Stikubank, 2026)
The high risk of fire at the AL Bumi IT Store, an electronics shop, without an automatic detection system requires a proactive monitoring solution. This research aims to design and implement an Internet of Things (IoT)-Based Fire Early Detection System with Database Integration and an Android Application for fast and accurate environmental monitoring. The system uses an ESP32 as the main microcontroller, which processes data from Temperature (DHT11), Smoke (MQ-2), and Fire (Flame Sensor) sensors. Environmental status data are transmitted in real time to a MySQL database and visualized through an Android application to facilitate remote monitoring by users. In addition, the system is equipped with local alerts in the form of LEDs and a buzzer. The implementation of this system is expected to minimize material losses and secure company assets by ensuring an instant and centralized emergency response.